Safety of low-dose aspirin in endovascular treatment for intracranial atherosclerotic stenosis. - Ning Ma; Ziqi Xu; Dapeng Mo; Feng Gao; Kun Gao; Xuan Sun; Xiaotong Xu; Lian Liu; Ligang Song; Tiejun Wang; Xingquan Zhao; Yilong Wang; et al. (PLoS ONE, 2014)
OBJECTIVES: To evaluate the safety of low-dose aspirin plus clopidogrel versus high-dose aspirin plus clopidogrel in prevention of vascular risk within 90 days of duration of dual antiplatelet therapy in patients treated with intracranial endovascular treatment. METHODS: From January 2012 to December 2013, this prospective and observational study enrolled 370 patients with symptomatic intracranial atherosclerotic stenosis of ≥70% with poor collateral undergoing intracranial endovascular treatment. Antiplatelet therapy consists of aspirin, at a low-dose of 100 mg or high-dose of 300 mg daily; clopidogrel, at a dose of 75 mg daily for 5 days before endovascular treatment. The dual antiplatelet therapy continued for 90 days after intervention. The study endpoints include acute thrombosis, subacute thrombosis, stroke or death within 90 days after intervention. RESULTS: Two hundred and seventy three patients received low-dose aspirin plus clopidogrel and 97 patients received high-dose aspirin plus clopidogrel before intracranial endovascular treatment. Within 90 days after intervention, there were 4 patients (1.5%) with acute thrombosis, 5 patients (1.8%) with subacute thrombosis, 17 patients (6.2%) with stroke, and 2 death (0.7%) in low-dose aspirin group, compared with no patient (0%) with acute thrombosis, 2 patient (2.1%) with subacute thrombosis, 6 patients (6.2%) with stroke, and 2 death (2.1%) in high-dose aspirin group, and there were no significant difference in all study endpoints between two groups. CONCLUSION: Low-dose aspirin plus clopidogrel is comparative in safety with high-dose aspirin plus clopidogrel within 90 days of duration of dual antiplatelet therapy in patients treated with intracranial endovascular treatment.